2014
DOI: 10.1155/2014/519203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organoboron Compounds on Ethylene Polymerization Using Cp2ZrCl2/MAO as Catalyst System

Abstract: Organoboron compounds of nonionic and ionic nature, tris(pentafluorophenyl)borane, and N,N-dimethylanilinium tetra(pentafluorophenyl)borate were evaluated to act in conjunction with MAO as activators on ethylene polymerization by using the catalyst Cp2ZrCl2. A decrease on the catalytic activity was observed in both cases in relation with a reference polyethylene which was synthesized in absence of any organoboron compound. An increase on the crystallinity degree and molecular weight, as well as an improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As previously mentioned, different kinds of catalyst systems based on neodymium, lutetium, or lanthanum have been reported for this purpose. Recently, our research group has worked with several kinds of catalysts based on zirconium and titanium to polymerize ethylene, but mainly neodymium to polymerize 1,3‐butadiene . Different purposes drove those works; nonetheless all of them evaluated different types of alkylaluminums and/or boron compounds as catalyst activators.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, different kinds of catalyst systems based on neodymium, lutetium, or lanthanum have been reported for this purpose. Recently, our research group has worked with several kinds of catalysts based on zirconium and titanium to polymerize ethylene, but mainly neodymium to polymerize 1,3‐butadiene . Different purposes drove those works; nonetheless all of them evaluated different types of alkylaluminums and/or boron compounds as catalyst activators.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, our research group reported the use of tris(pentafluorophenyl)borane and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate (B1 and B2 in this work, respectively) to act in conjunction with MAO as activators on ethylene polymerization by using the catalyst CP2ZrCl2. The addition of these organoboron compounds of ionic and nonionic nature in a molar ratio B1(or B2)/Zr = 5 promoted a partial deactivation of the catalyst, causing a reduction in the catalytic activity; however, the crystallinity degree, as well as the macromolecular, thermal and dynamic-mechanical properties of the obtained polyethylenes were improved, especially with B1 as co-activator in this evaluated catalytic system [14]. In the same context, González-Hernández et al [20] reported the ethylene polymerization using catalysts derived from Zr aluminohydride complexes activated with tris(pentafluorophenyl)borane (B1 in this work), although with limited utility (catalytic activity) of these catalysts systems when compared with the corresponding use of MAO as the activator.…”
Section: Introductionmentioning
confidence: 92%
“…A prominent alternative to replace MAO is the use of other bulky coordinating anions like organoboranes, such as tris(pentafluorophenyl)borane (B1) [9,10] and organoborates such as N,N-dimethylanilinium tetra(pentafluorophenyl)borate (B2) or trityl tetra(pentafluorophenyl)borate (B3) [11,12]. This type of activators can ionize the metallocene (pre-alkylated) catalyst, acting as Lewis acids, leading to excellent active cationic metallocene catalysts for the polymerization of olefins in quasi-equimolar amounts between the metallocene catalyst and the boron-based activator, and resulting in catalytic complexes with a definite chemical structure [13][14][15]. A breakthrough in this field was the introduction of the weakly coordinating tris(pentafluorophenyl)borate [B(C6F5)3] as a counterion, which can abstract a methyl group from the alkylated metallocene catalyst, to form ionic species such as [CP2ZrMe] + [MeB(C6F5)3] -, followed by the coordination of a monomer molecule and subsequent propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, our research group reported the use of tris(pentafluorophenyl)borane and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate (B1 and B2 in this work, respectively) to act in conjunction with MAO as activators on ethylene polymerization by using the catalyst CP 2 ZrCl 2 . The addition of these organoboron compounds of ionic and nonionic nature in a molar ratio B1(or B2)/Zr = 5 promoted a partial deactivation of the catalyst, causing a reduction in the catalytic activity; however, the crystallinity degree, as well as the macromolecular, thermal, and dynamic-mechanical properties of the obtained polyethylenes were improved, especially with B1 as co-activator in this evaluated catalytic system [14]. In the same context, González-Hernández et al [19] reported the ethylene polymerization using catalysts derived from Zr aluminohydride complexes activated with tris(pentafluorophenyl)borane (B1), although with limited utility (catalytic activity) of these catalysts systems when compared with the corresponding use of MAO as the activator.…”
Section: Introductionmentioning
confidence: 93%
“…A prominent alternative to replace MAO is the use of other bulky coordinating anions such as organoboranes, e.g., tris(pentafluorophenyl)borane (B1) [9,10], and organoborates such as N,N-dimethylanilinium tetra(pentafluorophenyl)borate (B2) or trityl tetra(pentafluorophenyl)borate (B3) [11,12]. These types of activators can ionize the metallocene (pre-alkylated) catalyst, acting as Lewis acids, leading to excellent active cationic metallocene catalysts for the polymerization of olefins in quasi-equimolar amounts between the metallocene catalyst and the boron-based activator, and resulting in catalytic complexes with a definite chemical structure [13][14][15]. A breakthrough in this field was the introduction of the weakly coordinating tris(pentafluorophenyl)borate [B(C6F5)3] as a counterion, which can abstract a methyl group from the alkylated metallocene catalyst, to form ionic species such as [CP2ZrMe] + [MeB(C6F5)3] − , followed by the coordination of a monomer molecule and subsequent propagation [10].…”
Section: Introductionmentioning
confidence: 99%